No advantage of Imatinib in combination with hydroxyurea over Imatinib monotherapy: a study of the East German Study Group (OSHO) and the German CML study group - Lange, Thoralf; Niederwieser, Christian; Gil, Arthur; Krahl, Rainer; Grünhagen, Ulrich von; Al-Ali, Haifa Kathrin; Jentsch-Ullrich, Kathleen; Spohn, Claudia; Lakner, Volker; Assmann, Michael; Junghanss, Christian; Cross, Michael; et al. (Leukemia and lymphoma, 2020)
Chronic myeloid leukaemia, imatinib, hydroxyurea/imatinib, outcome, phase I, phase II